Viral sequence determines HLA-E-restricted T cell recognition of hepatitis B surface antigen - Gavuthami Murugesan; Rachel L. Paterson; Rakesh Kulkarni; Veronica Ilkow; Richard J. Suckling; Mary M. Connolly; Vijaykumar Karuppiah; Robert Pengelly; Archana Jadhav; Jose Donoso; Tiaan Heunis; Wilawan Bunjobpol; et al. (Nature Communications)
Abstract The non-polymorphic HLA-E molecule offers opportunities for new universal immunotherapeutic approaches to chronic infectious diseases. Chronic Hepatitis B virus (HBV) infection is driven in part by T cell dysfunction due to elevated levels of the HBV envelope (Env) protein hepatitis B surface antigen (HBsAg). Here we report the characterization of three genotypic variants of an HLA-E-binding HBsAg peptide, Env371-379, identified through bioinformatic predictions and verified by biochemical and cellular assays. Using a soluble affinity-enhanced T cell receptor (TCR) (a09b08)-anti-CD3 bispecific molecule to probe HLA-E presentation of the Env371-379 peptides, we demonstrate that only the most stable Env371-379 variant, L6I, elicits functional responses to a09b08-anti-CD3-redirected polyclonal T cells co-cultured with targets expressing endogenous HBsAg. Furthermore, HLA-E-Env371-379 L6I-specific CD8+ T cells are detectable in HBV-naïve donors and people with chronic HBV after in vitro priming. In conclusion, we provide evidence for HLA-E-mediated HBV Env peptide presentation, and highlight the effect of viral mutations on the stability and targetability of pHLA-E molecules.